Pengetahuan SALT Triage Bisa Diperoleh Melalui Menonton Video Simulasi - Suratno; Amandus, Hieronimus; Rianti, Rima; Ifhan, Doni Al (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Background : Digital technology in the learning process is no longer a foreign object now. The existence ofhardware such as phones, computers, tablets, iPads and the like which are supported by the rapiddevelopment of the internet makes all information and communication more effective and efficient. The useof technology is expected to synergize and support conventional work. This study seeks answers aboutalternative learning models that can be used by nurses in increasing their knowledge of the triage masscasuality accidents in situations of lack of education and training that they get directly.Purposes : This study aims to determine the effect of watching SALT Triage simulation videos before andafter the intervention is carried out to increase the knowledge of emergency nurses in conducting SALTTriage simulations.Methods : This type of research is a nonequivalent control group design. Samples were taken using apurposive sampling technique with a large sample of 32 respondents divided into 2 groups. Data analysisusing paired t test.Result : There was an effect of watching SALT Triage simulation videos on increasing nurses' knowledgebefore and after the intervention with the results of p <0.05.Conclusion : Watching SALT Triage simulation videos is one method that can be used to increase nurses'knowledge of triage dealing with victims of mass traffic accidents